JERAT BUDAYA BUJUK-RAYU DALAM LAYAR KACA DESAIN KOMUNIKASI VISUAL - H. Istanto, Freddy (Institute of Research and Community Outreach - Petra Christian University, 2001)
The global community%2C including Indonesian society are trapped in the condition where cultural enticement through television has been spreading. With full capacity%2C the screen presents women as the main cast dancing and singing alluring theme to conquer society into consumptive culture. Women are always accused to be the leading actresses in this enticement and the cast securing their position in family. On the other hand%2C the puppeteers playing women on the screen are less spotlighted. Some of them are men and the others are visual communication designers. Abstract in Bahasa Indonesia : Tidak saja di Indonesia%2C warga duniapun kini berada dalam kondisi dimana budaya bujuk rayu lewat layar kaca demikian meruyak kemana-mana. Dengan segala kemampuannya%2C layar kaca menghadirkan perempuan sebagai pemeran utama menari dan mendendangkan bujuk rayu untuk menaklukan masyarakat pada budaya konsumer. Perempuan selalu dituding sebagai pelaku utama peran bujuk rayu ini dan pemeran yang melanggengkan posisinya pada seputaran lingkup rumah tangga. Di sisi yang lain%2C kurang di soroti tangan-tangan yang menggerakkan peran perempuan di layar kaca. Sebagian dari mereka adalah laki-laki dan sebagian dari mereka adalah para Desainer Komunikasi Visual. cultural enticement%2C women%2C television%2C visual communication design.